MicroRNA-320a inhibits proliferation and invasion of breast cancer cells by targeting RAB11A - Wang, Biyun (Am J Cancer Res, 2015)
MicroRNAs (miRNAs) are deregulated in many types of cancer including breast cancer (BC). miR-320a dysregulation has been associated with different malignancies although its prognostic significance remains unclear. Here, we examined the role of miR-320a in BC and explored the underlying mechanisms. Our results showed that miR-320a was significantly downregulated in BC cell lines and tissues, and its ectopic expression inhibited cell proliferation, migration, and invasion in vitro and tumor growth in a mouse xenograft model. We identified Rab11a as a direct target of miR-320a and showed that its expression was upregulated in tumor samples and inversely correlated with the expression of miR-320a. In BC cells, the downregulation of Rab11a through miR-320a was concomitant with the inactivation of Akt. Overexpression of Rab11a abrogated miR-320a-induced inhibition of BC growth and invasion. These results suggest that miR-320a may act as a tumor suppressor in BC through a mechanism involving the modulation of Rab11a expression and the activation of the Akt signaling pathway. miR-320a may therefore serve as a biomarker for BC, and the modulation of its expression may represent a novel therapeutic strategy in BC treatment.